Open Access Publishing in 2010: what publishers offer, what researchers want - First results of the SOAP project - Mele, Salvatore (Septentrio Conference Series, 2014)
The SOAP project (Study of Open Access Publishing http://soap-fp7.eu), describes and analyses the open access publishing landscape as well as exploring the risks and opportunities of the transition to open access publishing for libraries, publishers and funding agencies. Findings from the most detailed study so far of the current offering and success of gold open access journals, publishers and models will be presented, spotlighting the amazing difference between large and small publishing houses and learned societies, licensing practices and business models. The first results of a comprehensive survey of opinions and attitudes on open access of 50'000 researchers across all disciplines and around the world will be discussed. This largest survey to date shows that "one size does not fit all" in the open access need, attitudes and practices of researchers, and there is a myriad factors libraries, publishers and funding agencies have to consider to trace a path through these shifting sands. Note: The project, funded by the European Commission, comprise publishers (BioMed Central, SAGE Publication Ltd., Springer Science and Business Media), research institutions (CERN - European Organization for Nuclear Research, Max Planck Society) and funding agencies (STFC - Science & Technology Facilities Council UK).